PROGRAM FRAKSIONAL LINIER DENGAN KOEFISIEN INTERVAL - Sari, Annisa Ratna; ., Sunarsih; ., Suryoto (MATEMATIKA, 2014)
Linear fractional programming is a special case of nonlinear programming which the objective function is a ratio of two linear function with linear constraints. Linear fractional programming is used to optimize the efficiency of the activitiesÂ  of the other activities. In some case, coefficients of the objective function is uncertain. Therefore, It can be selected the interval numbers as coefficients. First step in solving linear fractional programming with interval coefficients in the objective function is transforming it into linear programming using the Charnes - Cooper method. The result of the transformation is linear programming with interval coefficients (LPIC). To solve the LPIC is used method proposed by K Ramadan. In this method, LPIC converted into two linear programming that obtains the best optimum solution and the worst optimum solution, respectively. This optimum solution is the optimum solution for linear fractional programming problem with interval coefficients in the objective function.